Impact of Pain on Incident Risk of Disability in Elderly Japanese: Cause-specific Analysis. (April 2017) - Kaiho, Yu; Sugawara, Yumi; Sugiyama, Kemmyo; Tomata, Yasutake; Endo, Yasuhiro; Toyama, Hiroaki; Yamauchi, Masanori; Tsuji, Ichiro
Abstract : Background: Although several cross-sectional studies have reported that pain is associated with functional disability in the elderly, data regarding a longitudinal association between pain and disability are inconsistent. This study aimed to investigate the association of pain severity with subsequent functional disability due to all causes as well as stroke, dementia, and joint disease/fracture. Methods: The authors conducted a prospective cohort study of 13, 702 Japanese individuals aged 65 yr or older. Information regarding pain severity during the previous 4 weeks and other lifestyle factors was collected via questionnaire in 2006. Data on the incidence of functional disability were retrieved from the Long-term Care Insurance database. Cox proportional hazards regression analysis was used to estimate the multivariate-adjusted hazard ratios for incident functional disability. Results: The authors documented 2, 686 (19.6%) cases of incident functional disability. The multivariate hazard ratio of functional disability was 1.15 (95% CI, 1.02 to 1.31) among respondents with moderate pain and 1.31 (95% CI, 1.12 to 1.54) among respondents with severe pain in comparison with those without pain ( P trend < 0.001). These positive associations were particularly remarkable for disability due to joint disease/fracture: the multivariate hazard ratio was 1.88 (95% CI, 1.37 to 2.58) for moderate pain and 2.76 (95% CI, 1.93 to 3.95) for severe pain ( P trend < 0.001). There was a negative association between pain severity and disability due to dementia ( P trend = 0.041) and no significant association between pain severity and disability due to stroke. Conclusions: Among elderly Japanese individuals, the authors found a significant positive association between pain severity and future incident functional disability. Abstract : Moderate pain increased the risk of functional disability by 15% and severe pain increased the risk by 31%. Risk was especially great for joint disease and fractures.